Foundations of augmented cognition. neuroergonomics and operational neuroscience : 10th international conference, AC 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016 : proceedings /: neuroergonomics and operational neuroscience : 10th international conference, AC 2016, held as part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016 : proceedings. Part I : (2016) - Unknown
No abstract available